(untitled) (Publicaciones en Ciencias y Tecnología, 2007)
An evaluation approach based on the Analytical Hierarchic Process (AHP) for Content Management Systems (CMS) is presented. Traditionally, CMS comparison methods are non quantitative, dealing with a list of attributes that should be present for it to be well-established. Today, over 2000 CMS are available under the General Public License (GPL), making the task for an organization to objectively assess its alternatives, not a trivial one. A weighted evaluation tool for CMS based on the AHP is proposed , where weights are assigned to features according to their relevance, and a quantitative evaluation index is produced through a weighted average. This approach proved to be a useful tool allowing for a better CMS selection biased on the organization’s needs.